Spatial Distribution of Citrus Leprosis Associated with its Vector and Abiotic Factors in Different Cropping Systems - de Oliveira, Fabio Júnior; Farias, Paulo Roberto Silva; da Silva Noronha, Aloyséia Cristina; Maldonado, Walter [UNESP]; Cardoso, Luiz Antonio Soares (Friends Science Publishers, 2023)
Citrus leprosis stands out as one of the main phytosanitary problems found in citrus growing, being transmitted by the citrus leprosis mite Brevipalpus spp. The objective of this work was to characterize the spatial distribution of citrus leprosis and its vector associated with abiotic factors in two orange cultivation systems. The areas were selected from a previous survey of the occurrence of the vector and the disease in orange groves in the municipality of Capitão Poço, State of Pará. Estimates were performed on 112 georeferenced plants in a citrus plot in a monoculture system and 112 plants in a plot intercropped with teak from September 2015 to August 2016, at monthly intervals. Using a pocket magnifying glass with 10x magnification, the mite (Brevipalpus spp.) was counted on 3 fruits, 3 branches and 3 leaves of the inner and outer part of each plant. The symptoms of citrus leprosis were visually evaluated throughout the canopy of the plant. Most of the abiotic factors were associated with the occurrence of the leprosis mite in the region. Climatic variables influence citrus leprosis mite infestation and were not associated with disease incidence in both cropping systems. Higher maximum temperatures favored the infestation of mites, while precipitation was not the most determining factor in the population of mites. Citrus leprosis and its vector showed aggregated distribution in both areas. The kriging maps indicated that there was no association between citrus leprosis infection and its vector infestation in the two cropping systems
Keywords: Brevipalpus spp.; CiLV; Geostatistics; Kriging; Semivariogram